Assessment of Systemic Immune-inflammation Index Levels in Patients with Retinal Vein Occlusion. (16th March 2023) - Zuo, Wen; Chen, Ting; Song, Jiayi; Ai, Ming
ABSTRACT: Purpose: To assess the predictive value of inflammatory markers calculated from complete blood counts in patients with retinal vein occlusion (RVO). Methods: This was a retrospective cross-sectional study with a total of 56 RVO patients and 56 age- and gender-matched controls involved. All subjects went through a routine ocular examination, and the peripheral venous blood samples were collected to analyze the differences in inflammatory markers between groups. Results: The systemic immune-inflammation index (SII) and neutrophil-to-lymphocyte ratio (NLR) values were significantly higher in RVO patients than those in the controls (p=0.002, p=0.004, respectively). According to the receiver operating characteristic (ROC) curve analysis, the areas under the curve (AUC) of SII was 0.666. The AUC of NLR was 0.657. Conclusion: As a novel inflammatory indicator, SII is a more promising indicator than NLR and PLR in the prediction of RVO development.